Modern Tanscriptome Data Rrocessing Algorithms: a Review of Methods and Results of Approbation - M. V. Sprindzuk; L. V. Mozharovskaya; A. P. Konchits; L. P. Titov (Цифровая трансформация, 2021)
Analysis of bioinformatics data is an actual problem in modern computational biology and applied mathematics. With the development of biotechnology, as well as tools for obtaining and processing information derived from biological objects and systems, unresolved issues of the development and application of new algorithms and software have emerged. The authors propose practical algorithms and methods for processing transcriptome data for effective results of annotation, visualization and interpretation of data.